Seletividade de inseticidas utilizados em cultura algodoeira para o predador Cycloneda Sanguinea (Linnaeus, 1763) (Coleoptera, Coccinellidae) - Pedroso, Elizabeth do Carmo (2008)
The preservation of natural enemies in agroecosystems is very important to the pest control and thereat it should opt by the preferential application of selective products. In this way, the objective was evaluate the insecticides effects used in the cotton crop on the eggs, larvae from third-instar, pupae and adults from ladybug Cycloneda sanguinea (Linnaeus, 1763) and in the following development phases of this predator. The products used in g a.i. L-1 of water were triflumuron (Certero 480 SC - 0.048), spinosad (Tracer 480 SC - 0.24), chlorfenapyr (Pirate 240 SC - 1.2), chlothianidin (Focus 500 WP - 0.33) and imidacloprid/ß-cyfluthrin (Connect 100/12.5 SC - 0.33/0.042). The distilled water was used as control. All the pulverizations were applied directly on the eggs, larvae from third-instar, pupae and predator´s adults by Potter´s tower. The bioassays were realized at 25 ± 2ºC, RU 60 ± 10% and photophase of 12h. It was evaluated the embryonic period and viability from eggs directly treated; survival and duration of larvae from third-instar and pupae directly treated; survival from adults directly treated; survival and duration from stage of larval development, duration and survival in the pupal phase, sexual ratio and reproductive parameters of adults descendants from eggs, larvae from third-instar, pupae and adults directly treated. Triflumuron was selective to the eggs, as well its following development stages, but it was slightly prejudicial to the eggs and larvae from third-instar of C. sanguinea, however, it was selective to the pupae, as well its following development stages. The insecticides triflumuron and spinosad were slightly prejudicial to predator´s adults. Chlorfenapyr, chlothianidin and imidacloprid/ß-cyfluthrin were toxic to the eggs, larvae from third-instar, pupae and adults from C. sanguinea, as well its following development stages.